Back to Black : Black in Current Painting. - Görner, Veit; Bernasconi, Eveline; Käding, Caroline; Moll, Frank - Thorsten; Hieber, Lutz; Kestnergesellschaft, Hannover (Hannover : Kehrer Verlag, 2008)
Alonso, Pablo ; Avotins, Janis ; Boehm, Armin ; Bujnowski, Rafal ; Butzer, André ; Haager, Philipp ; Hildebrandt, Gregor ; Hofer, Andreas ; Krisanamis, Udomsak ; van Lankveld, Rezi et al.
Back to Black Black in Current Painting, Kestnergesellschaft, Hannover, May 30th - August 10th
kunstcatalogus